ARTISTIC IMAGE IN UZBEKISTAN LITERATURE AND IT’S IMPROVEMENT (International journal of artificial intelligence, 2026)
This article reflects the relationship between the theme and the image in poetry. The definitions of the artistic image in literary criticism are discussed, and the classification of images in the poetry of Azim Suyun is presented.